Fluid administration during routine colonoscopy is not clinically significant: a randomized controlled trial. Issue 12 (30th September 2021) - Ganguly, Timothy; Bierton, Christopher; Islam, Asif; Chan, Lily; Smithers, Lisa; Murphy, Elizabeth
Abstract: Background: Retrospective studies have questioned the benefits of intravenous (IV) fluids during routine colonoscopies given they are performed on well patients who experience limited fluid loss, consume clear fluids up until 2 h prior and low IV volumes typically infused. This trial aims to assess the impact of IV fluid on hypotension and electrolyte changes amongst patients undergoing colonoscopy. Methods: Participants undergoing colonoscopies were randomized (single blinded) to IV fluid or no IV fluid. Primary outcomes were equivalence of intraoperative hypotensive episodes (>20% drop in systolic blood pressure (SBP)) and changes in serum electrolytes post procedure. Secondary outcomes included patient reported outcome measures (PROMs). Results: Of the 470 participants enrolled, 84/235 (35.7%) from the IV fluids group and 88/230 (38.3%) from the no IV fluids group experienced a hypotensive event (difference in prevalence −2.5, 95% CI −11.3, 6.3). Fourteen participants in each group required clinical intervention to provide haemodynamic support (difference in prevalence −0.1, 95% CI −4.4, 4.2). Postoperative electrolytes changes and PROMs were similar for both groups. Conclusion: Whilst definitive recommendations for IV fluid use during routine colonoscopy are not possible as this trial was underpowered to show equivalence between the groups for hypotensive events, there was no clinically meaningful difference between the groups. These findings provide important data for meta‐synthesis and for planning future work. Abstract : This randomized controlled trial was designed to determine equivalence between those undergoing colonoscopy both with and without IV fluids. Whilst the study was underpowered to detect a difference no clinically significant difference was detected between our two cohorts. This study provides important data for further work in this area.